Nature's chemicals the natural products that shaped our world - Firn, Richard (Oxford : Oxford University Press, 2010)
This monograph describes natural products as a group in an evolutionary context. It synthesizes a widely dispersed literature and provides a general picture of natural products encompassing evolution, history, ecology, and environmental issues, along with some deeper theory relevant to biochemistry.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Natural products; Bioactive compounds